Stalin and the bomb : the Soviet Union and atomic energy 1939 - 1956 - Holloway, David, 1943- 1943- (Yale University Press, 1994)
In engrossing detail, David Holloway tells us how Stalin launched a crash atomic program only after the Americans bombed Hiroshima and showed that the bomb could be built; how the information handed over to the Soviets by Klaus Fuchs helped in the creation of their bomb; how the scientific intelligentsia, which included such men as Andrei Sakharov, interacted with the police apparatus headed by the suspicious and menacing Lavrentii Beria; what steps Stalin took to counter U.S. atomic diplomacy; how the nuclear project saved Soviet physics and enabled it to survive as an island of intellectual autonomy in a totalitarian society; and what happened when, after Stalin's death, Soviet scientists argued that a nuclear war might extinguish all life on earth